Analisis dan Perancangan Aplikasi e-dikbangspes Berbasis Web Pada Biro Sumber Daya Manusia Polda Sumatera Selatan: Analisis dan Perancangan Aplikasi e-dikbangspes berbasis web pada Biro Sumber Daya Manusia POLDA Sumatera Selatan - Miko Hardian; Aan Restu Mukti (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
The South Sumatra Regional Police is a government agency engaged in the field of security, securing/sharing the community and enforcing the law, as well as providing protection, security, protection and community services in the context of maintaining domestic security. Based on the research and analysis carried out, several problems were found, including the HR Selection Subdivision for the South Sumatra Police HR Bureau, which carried out data collection that had carried out the development of specialist education from year to year using a manual data collection system using Excel recap. In order to improve services and make work effective, a system for processing or recording data electronically was developed so that the information data obtained was accurate and fast, the Education and Special Education Bureau for Human Resources applications can be successfully built using the PHP programming language with the CodeIgniter framework. This shows that choosing the right technology can support reliable and efficient application development. the development of edikbangspes at the South Sumatra Polda HR Bureau using the Action Research method has brought benefits in improving service to internal employees. In the application design and development process, the active involvement of personnel is essential to ensure their needs and expectations are met. By hosting applications on the internet, edikbangsppes applications can be accessed by data input operators without time and location limitations. So with the development of the e-dikbangsppes information system, it is able to overcome problems related to personnel data collection which in this system can be accessed online or online personnel recording wherever and whenever, then based on evaluation results using the speed test application, web results obtained with an average score of 84.3 in the good category